Culture of controlling moral state of public opinion in the emergency situations («Public relations») - Remizov Вячеслав Александрович (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
This article deals with the description of the main directions of «public relations». Specific peculiarities of connection with the people in crisis and emergency situations were considered.